(untitled) (World Bulletin of Social Sciences, 2023)
This article summarizes the conclusions drawn from the results of scientific research conducted by scientists in this field, about the common origin of the science of philosophy and philosophical education. A general explanation of the concept of the philosophy of education is given and the conceptual significance of this science and direction in the modern educational process is investigated